2020
DOI: 10.1186/s10020-020-00180-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of uncoupling protein (Ucp) gene polymorphisms with cardiometabolic diseases

Abstract: The hereditary aspect of obesity is a major focus of modern medical genetics. The genetic background is known to determine a higher-than-average prevalence of obesity in certain regions, like Oceania. There is evidence that dysfunction of brown adipose tissue (BAT) may be a risk factor for obesity and type 2 diabetes (T2D). A significant number of studies in the field focus on the UCP family. The Ucp genes code for electron transport carriers. UCP1 (thermogenin) is the most abundant protein of the UCP superfam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 188 publications
(219 reference statements)
1
14
0
2
Order By: Relevance
“…Second, only the ADRB3 gene polymorphism was analyzed as a candidate gene for overweight and obesity in this relatively small genome cohort. However, several other obesity‐related candidate genes exist, such as leptin, leptin receptor, melanocortin 4 receptor, 1 , 2 uncoupling protein‐1, 45 and fat mass and obesity‐associated protein (FTO) 46 were not taken into account. Furthermore, investigations are required to elucidate the genetic factors associated with obesity using a large‐scale sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Second, only the ADRB3 gene polymorphism was analyzed as a candidate gene for overweight and obesity in this relatively small genome cohort. However, several other obesity‐related candidate genes exist, such as leptin, leptin receptor, melanocortin 4 receptor, 1 , 2 uncoupling protein‐1, 45 and fat mass and obesity‐associated protein (FTO) 46 were not taken into account. Furthermore, investigations are required to elucidate the genetic factors associated with obesity using a large‐scale sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that excessive accumulation of ROS may lead to the abnormal development of the embryonic heart through irreversible damage to cell membranes, DNA, and other cellular structures 13 , 21 , 35 . Meanwhile, excessive accumulation of ROS also may exert cytotoxic effects in cardiomyocytes, thereby resulting in the abnormal development of the embryonic heart 21 , 36 . In a word, findings from the present study support our results.…”
Section: Discussionmentioning
confidence: 99%
“…The UCP3 -55C/T promoter variant is of interest because of its position at 4 bp downstream of a peroxisome proliferator-activated receptor (PPAR) responsive region, which could modify PPAR-dependent responsiveness [ 66 ]. Thus, many studies have linked this polymorphism to the regulation of lipid metabolism and insulin sensitivity [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%